The Level of Emotional Intelligence of English Language Students with Learning Disabilities from the Point of View of Their Parents (Global Journal of Human-Social Science, 2021)
Emotional intelligence is an important factor in the well-being of students, whether regular students or students with learning disabilities. The category of students with LDs always face challenges to adapt and adjust in society and in the school environment. This study aimed at revealing the emotional intelligence of English language students with learning disabilities in Aseer region. The study sample consisted of (140) students with learning difficulties. To achieve the objectives of the study, the emotional intelligence questionnaire was developed and consisted of (45) items, divided into five areas: knowledge of emotions, emotional management, sympathy, empathy, and social competence. The validity and reliability of the questionnaire was ensured before application and data analysis. The results showed that the overall degree of emotional intelligence among students with learning disabilities was low. The results also found that regular students have higher emotional intelligence than students with LDs. The study recommended developing training programs to develop emotional intelligence for students with learning difficulties, and conducting a descriptive and experimental study dealing with other types of intelligence among students with learning disabilities and other special education categories and comparing them with regular students.
Keywords: emotional intelligence; english language; students with learning difficulties